Does social media marketing affect brand awareness? A study of cosmetic products among gen z in Kuala Lumpur - Lim, Zhi Wei; Yong, Yeu Chin (2023)
In this era of rapid technological advancement, the number of consumers browsing online information is steadily increasing. Social media platforms have emerged as a vital channel for communication and sharing information, making them the greatest option for conducting business. This research paper examined how social media marketing influences the level of brand recognition for cosmetic items among Generation Z individuals in Kuala Lumpur. Upon the completion of the research, five independent variables have been investigated which incorporate entertainment, customization, trendiness, interaction and E-WOM. The researchers have addressed the problem regarding to the lack of existing study on discussing about the factors affecting the brand awareness of cosmetic products. Thus, the objective of this research is mainly to determine the effect of social media marketing on brand awareness of cosmetic products among Gen Z in Kuala Lumpur. The sample size that defined for this study is comprised of 275 respondents, mainly focusing on Malaysian Generation Z (GenZ) consumers that aged between 9 and 24 years old as the target populations, through the use of snowball sampling technique. The data gathered were analyzed through the utilization of the Statistical Package for Social Sciences. This research also highlighted implications, acknowledged limitations, and provided recommendations as points of reference for upcoming entrepreneurs, researchers, and individuals.